Specific absorption rate investigation of different EBG-M applicator structures for non-invasive hyperthermia cancer treatment procedure - Lias, K.; Buniyamin, N.; Ahmad Narihan, M.Z (Springer-Verlag, 2016)
The paper presents the results of an investigation of the effects of specific absorption rate (SAR) when applicators (antennas) are used in non-invasive hyperthermia cancer treatment procedure. Several different applicator structures were constructed and the SAR simulation was observed. Rectangular and circular microstrip applicators were initially designed, and then an EBG and water bolus structure was integrated with the applicator. This applicator termed EBG-M applicator was constructed and its SAR simulation was observed using the SEMCAD X solver software. The results indicated that the EBG-M applicators provided better SAR distribution pattern, where the EBG-M with rectangular structures offered better focusing capability, which reduced the unwanted hot spots at the surrounding healthy tissues. Meanwhile, the EBG-M with circular structure obtained better penetration depth. In addition, when the water bolus is added to the structure, it resulted in shaping the SAR contour and provided a cooler environment which then reduced the skin burn problem during the treatment.